1996
DOI: 10.1111/j.1651-2227.1996.tb14087.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry, bronchodilator test or symptom scoring for the assessment of childhood asthma

Abstract: The value of spirometry, the bronchodilator test and 2 weeks' symptom scoring for the assessment of the severity of childhood asthma was studied in a series of 65 consecutively referred school-aged asthmatic children, with the diurnal peak expiratory flow (PEF) variability in home recordings serving as a golden standard. The amplitude of the peak expiratory flow rate (PEFR) variation could be best predicted by the baseline forced expiratory volume in 1 s (FEV1) and the past history of the symptom rate, the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…In previous studies, 17±26% of asthmatic children have had decreased MMEF, 29% diagnostic rises in MMEF, 2% decreased PEF, 8% decreased FEV1, and 48% a >20% diurnal variation in PEF [9,12,16,17]. In a recent study from northern Finland, 23% of children had a significant rise in FEV1 and 29% in MMEF values [12]. Thus, our results speak for a good treatment control, better than in most previous studies, in children of all treatment groups.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In previous studies, 17±26% of asthmatic children have had decreased MMEF, 29% diagnostic rises in MMEF, 2% decreased PEF, 8% decreased FEV1, and 48% a >20% diurnal variation in PEF [9,12,16,17]. In a recent study from northern Finland, 23% of children had a significant rise in FEV1 and 29% in MMEF values [12]. Thus, our results speak for a good treatment control, better than in most previous studies, in children of all treatment groups.…”
Section: Discussionsupporting
confidence: 64%
“…The most sensitive variable, MMEF, was decreased in 17%, and it rose significantly in the bronchodilatation test in 10% of the subjects. In previous studies, 17±26% of asthmatic children have had decreased MMEF, 29% diagnostic rises in MMEF, 2% decreased PEF, 8% decreased FEV1, and 48% a >20% diurnal variation in PEF [9,12,16,17]. In a recent study from northern Finland, 23% of children had a significant rise in FEV1 and 29% in MMEF values [12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast with challenge tests, BD responsiveness is easily and safely obtained and reliably measured in epidemiologic studies (5,6). A previous study also has indicated that the BD responsiveness is correlated with the severity of asthma (7).…”
Section: Introductionmentioning
confidence: 94%
“…Smaller airway airflow is reflected in the average forced expiratory flow rate between 25 and 75 percent (FEF 25%-75% ) , which also is called the maximum mid-expiratory flow rate (MMEFR) (Bertka, 2002;Linna, 1996). There is some indication that FEF 25%-75% may be more sensitive in indicating early airway obstruction, particularly in small airways (Lebecque, Kiakulanda, & Coates, 1993;McFadden, & Linden, 1972;Ratageri, Kabra, Lokha, Dwivedi, & Seth, 2001).…”
Section: Health Statusmentioning
confidence: 96%